How costly is "clean"?: an analysis of the benefits and costs of superfund site remediations - Hamilton, James T.; Viscusi, W. Kip (1999)
The cleanup of hazardous waste sites under the U.S. Environmental Protection Agency's Superfund program is governed by a number of legislative and regulatory constraints. Congress passed legislation in 1986 directing the Environmental Protection Agency (EPA) to pursue permanent remedies that embodies stringent cleanup standards. The agency has chosen to use conservative assumptions in risk assessments at hazardous waste sites, including a presumption that on-site risks for hypothetical future residents should be calculated in the site remediation process. This article offers the first comprehensive assessment of the cost-effectiveness of these Superfund cleanups. Our results reveal that many EPA Superfund remediations fail a partial benefit-cost test. For a sample of the 150 Superfund sites, we find that at the majority of sites the expected number of cancers averted by remediation is less than 0.1 cases per site and that the cost per cancer case averted is over $100 million. The analysis demonstrates the importance of explicitly calculating the trade-offs embodies in environmental cleanup decisions. - Reproduced
Keywords: Wastes